DEVELOPMENT OF PHENOLICS PRODUCTION FROM RICE BRAN AS FUNCTIONAL FOOD INGREDIENT - Mardiah, Zahara
The process of milling rice into rice produces by-products, one of which is rice bran. As a rice-producing country with a production of 54.7 million tonnes/year, the availability of rice bran in Indonesia reaches 5.4 million tonnes/year. Rice bran has received attention in the world of functional food because it has a high bioactive content, especially phenolic compounds. The phenolic content in rice bran is on par with fruits and vegetables with high antioxidant activity. However, rice bran has not been utilized properly and even rice bran is still mostly sold only as animal feed. Rice bran utilization technology is needed to increase its economic value. Therefore, the general research objective is to develop a technology for the production of phenolics from rice bran as a functional food ingredient. The first stage of the research begins with stabilizing rice bran. Rice bran easily becomes rancid as a result of lipase activity, so its use as food is limited. The purpose of the first stage of research is to minimize rancidity in rice bran. The stabilization process was carried out using lab-scale natural convective (KA) and forced convective (KP) ovens and minipilots. The stabilization temperatures applied were 70, 90, 110 and 160°C for 10, 30 and 60 minutes. Observations made were water content, lipase activity, phenolic content and antioxidant activity. The results showed that stabilization using KP at 160°C for 60 minutes was the best treatment. Under these stabilization conditions, lipase activity decreased by 74±1.4%, and increased phenolic and antioxidant activity by 12.5±2.7 and 8.8±0.02%, respectively. In addition, the model for drying rice bran using the KP oven was also obtained. The diffusivity of water in rice bran depends on temperature (T) so that the value of the diffusivity coefficient of water in rice bran is made in the form of the equation 3.4x10-6 m2/s. This model can be used to determine the optimal conditions for drying rice bran using a convective oven. The results of the research at this stage produced stabilized rice bran. The next step is to perform phenolic extraction from stabilized rice bran. This stage is intended to obtain an extraction method that produces extracts with the highest phenolic content. The research was conducted by comparing conventional extraction methods, namely maceration with non-conventional extraction methods, namely ultrasonic and microwave assisted. The best extraction method is then optimized for operating conditions using the response surface method (RSM) approach. The results of the research at this stage showed that the phenolic content of the microwave-assisted method was higher than maceration and ultrasonic-assisted, namely 8.39±0.05, 8.29±0.02, and 8.28±0.03 g phenolic/100 g rice bran. Therefore, the microwave assisted method was chosen to optimize the operating conditions. Optimization parameters include ethanol concentration (%), extraction time (minutes), and microwave power (W). The optimum operating conditions were found to be an ethanol concentration of 80%, a microwave application time of 1.96 minutes, and a microwave power of 180 W, which resulted in free, bound, and total phenolic contents of 2.29±0.03, 6.73±0.4, and 9.01±0.04 g phenolic/100 g rice bran, respectively. This stage of the research extracted 95% of the phenolics present in the rice bran. In addition, an rice bran phenolic extraction using the microwave-assisted method was succesfully modelled with an R2 value of 0.96. The obtained phenolic diffusivity value was 5.97x10-10 m2/s, and the distribution constant value was 0.94. The extraction model is useful in optimizing the extraction conditions of phenolics and predicting the effects of some parameters on the extraction performance. The phenolic extract solution obtained in this second stage had a purity of 4.6% for free phenolic extracts and 0.2% for bound phenolic extracts. The next stage aimed to increase the purity of the phenolic extract solution using the adsorption-desorption method. This research stage includes the selection of the adsorbent, determination of the adsorption isotherm characteristics, determination of the optimal flow rate in dynamic adsorption-desorption, modeling of the breakthrough curve in the phenolic adsorption process, and determination of the purity of the phenolic extract before and after purification. The types of adsorbents tested were ICD anions (basic anion exchangers), ICD cations (acid cation exchangers), KH80 cations (acid cation exchangers), LJ11 (nonpolar) and LJ18 (semipolar). The results showed that the best adsorbent in purifying rice bran phenolic extract was LJ18. This adsorbent has an adsorption ratio of 82.8%, a desorption ratio of 94.3% and a yield recovery of 78%. The Langmuir isothermal adsorption model can describe the rice bran phenolic adsorption system well where the R2 value reaches 0.99, while the Langmuir constant (KL) value obtained is 0.03 L/mg and the maximum adsorption capacity value (qm) is 0.7 mg/g . The dynamic adsorption-desorption results showed that the adsorption flow rate of 4 bv/h (bed volume per hour) and the desorption flow rate of 3 bv/h were the best flow rates based on high efficiency and short working time. The breakthrough curve of the rice bran phenolic adsorption process on the LJ18 adsorbent was successfully modeled with an R2 value of 0.99. The breakpoint point was obtained in the 280th minute. The increase in the purity of the free phenolic extract reached 1.8 times from 4.58±0,06 to 12.79±0,3 g phenolic/g dry extract. Meanwhile, the increase in purity of the bound phenolic extract reached 58.3 times from 0.22±0,01 to 12.65±0,2 g phenolic/g dry extract. Then the free and bound phenolic extract solutions were combined to produce a concentrated rice bran phenolic extract solution. In the final stage of the research aimed at encapsulating the phenolic extract so that it is stable during storage. Encapsulation was carried out with three coating agent treatments namely maltodextrin (MD), gum arabic (GA), and a combination of maltodextrin and gum arabic (MD/GA). In addition, samples without encapsulation (TP) were also prepared as a comparison. The encapsulation method uses a freeze dryer (F) and a spray dryer (S). The resulting powder was then stored for 4 weeks where phenolic analysis and antioxidant activity were carried out every week of storage. The results showed a 46% decrease in phenolic in the extract without encapsulation, while the decrease in phenolic in the encapsulated extract ranged from 9–12%. The S-MD/GA treatment was the best treatment because it was able to maintain the phenolic content of the extract and antioxidant activity by 92 and 84% respectively without any significant decrease during storage (p<0.05). The results of the analysis of the IC50 value of S-MD-GA was 0.7±0.02 mg phenolic/mL while the IC50 value of the positive control (ascorbic acid) was 0.6±0.01 mg phenolic/mL, thus the relative antioxidant activity (RAA) value of phenolic rice bran was 0.86. Mass balance calculations show that processing 1 ton of raw rice bran will produce 0.26 tons of encapsulated phenolic extract powder consisting of 0.13 tons of phenolic extract and 0.13 tons of MD/GA coating agent. This technology will provide new opportunities for the industrial world in the development of new products based on rice by-products, namely rice bran.